Improving assessment equity using Interactive Oral Assessments - Krautloher, Amita (Journal of University Teaching and Learning Practice, 2024)
Equity in assessment has been a major issue plaguing the higher education sector for a long time and although efforts have been made to implement a variety of assessments to address this issue, the assessment design tends to ignore the increasingly diverse student population. This article assesses the equity of Interactive Oral Assessments (IOAs) based on the principles of the McCES framework: match, comprehensible, challenge, elicit, and scaffold. Accordingly, the process of designing and administering IOAs is compared with each of the five principles and shows that the assessment environment for students from equity backgrounds is significantly improved. To do this, the data collected from teaching staff and students from a two-year mixed methods research project at a regional university in Australia is used to evaluate the claim. The findings demonstrate that IOAs offer an opportunity to assess students’ learning and clarify their ability to achieve learning outcomes which aligns with the McCES framework; therefore, it is argued that IOAs are an equitable assessment approach. The implications of the findings for academics, students, and educational institutions are significant. For academics, they can be confident that their assessment approach is equitable. For non-traditional students, the chances of succeeding in assessments and improvement in learning are enhanced. For educational institutions, a direct impact on reducing the gap between the performance of mainstream students and non-traditional students in relation to retention, attrition, and successful completions is expected.